Audio effects : theory, implementation and application - Reiss, Joshua D.; McPherson, Andrew, 1982- (CRC Press, 2015)
PrefaceAbout the AuthorsAim and Scope of BookIntroduction and FundamentalsUnderstanding Sound and Digital AudioWorking with DecibelsLevel MeasurementsRepresenting and Understanding Digital SignalsRepresenting Complex NumbersFrequency and Time-Frequency RepresentationsAliasingModifying and Processing Digital SignalsThe Z Transform and Filter RepresentationDigital Filter ExampleNonlinear and Time-Varying EffectsDelay Line EffectsDelayTheoryBasic DelayDelay with FeedbackOther Delay TypesSlapback DelayMultitap DelayPing-Pong DelayImplementationBasic DelayVariationsDelay Line InterpolationCode Exam.